Highly frustrated liquid crystal phases in optically active dimers: synthesis and rich phase transitional behavior - Nayak, R. A.; Bhat, S. A.; Shanker, G.; Rao, D. S. S.; Yelamaggad, C. V. (New Journal of Chemistry, 2019)
Herein we report on the synthesis and characterization of four new series of optically active, nonsymmetric dimers in which cholesterol is covalently linked to a Schiff base core through an ω-oxyalkanoyl spacer. While the Schiff base core is substituted with n-butyloxy, n-hexyloxy, n-octyloxy, n-decyloxy and n-dodecyloxy tails, three even-parity spacers, namely, 4-oxybutanoyl, 6-oxyhexanoyl, 8-oxyoctanoyl, and an odd-parity spacer, namely, 5-oxypentanoyl, have been used to join the two cores. The experimental results show that the length and parity of the spacer and the length of the terminal tail play a vital role in deciding the phase sequences of the dimers. In general, the dimers possessing an even-parity spacer display enantiotropic LC phases such as chiral nematic (N*), twist grain boundary (TGB), smectic A (SmA), chiral smectic C (SmC*) and twist grain boundary phase with SmC* slabs (TGBC*). Some of these dimers display TGBC* over a wide temperature range. The dimers with an odd-parity (5-oxypentanoyl) spacer display, unlike their even-membered counterparts, blue phases (BPIII/II/I); besides, they stabilize N* and/or unknown smectic (SmX) phases. The circular dichroism (CD) measurements were carried out as a function of temperature on the planar texture formed by three even-membered dimers and an odd-membered dimer. The occurrence of a strong negative CD band in the N* phase of the even-membered dimers suggests a left-handed screw sense of the macroscopic helical structure, and the scenario is opposite in the case of an odd-membered dimer.